INVESTIGATION OF IMPREGNATED ACTIVATED CARBON PROPERTIES USED IN HYDROGEN SULFIDE FINE REMOVAL - Isik-Gulsac,Isil (2016)
Abstract The effects of relative humidity (RH), carbon dioxide (CO2), methane (CH4), oxygen (O2) presence and gas hourly space velocity (GHSV) on H2S adsorption dynamics of KOH/CaO impregnated activated carbon are investigated in this study. X-ray diffraction (XRD), scanning electron microscopy with energy dispersive X-ray detector (SEM-EDX), thermogravimetric analysis (TGA), and Fourier Transform Infrared Spectroscopy (FTIR) techniques are applied and nitrogen adsorption characteristics are determined for characterization. The presence of water, O2 and lower GHSV has beneficial effects on the activated carbon performance. CO2 decreases the adsorption capacity due to its acidic characteristics. Best adsorption capacity is obtained as 13 wt % in KOH/CaO impregnated activated carbon, in a CH4 (60%)/CO2 (38%)/O2 (2%) gas atmosphere, at ambient temperature, RH 90 and 5000 h-1 GHSV. Sulphur species formation was verified with the help of SEM-EDX, XRD, TGA, FTIR and nitrogen adsorption analysis on the exhausted samples.